Banding Together : How Communities Create Genres in Popular Music - Lena, Jennifer C. (Book collections on Project MUSE., 2012)
Why do some music styles gain mass popularity while others thrive in small niches? Banding Together explores this question and reveals the attributes that together explain the growth of twentieth-century American popular music. Drawing on a vast array of examples from sixty musical styles--ranging from rap and bluegrass to death metal and South Texas polka, and including several created outside the United States--Jennifer Lena uncovers the shared grammar that allows us to understand the cultural language and evolution of popular music.